Analytical Determination of Nicotine and Tar Levels in Various Dokha and Shisha Tobacco Products. Issue 7 (10th May 2018) - Mahboub, Bassam; Mohammad, Ayesha Begum; Nahlé, Ayssar; Vats, Mayank; Al Assaf, Omar; Al-Zarooni, Hamdan
Abstract: In the Middle East, there is no precise data and literature on tobacco-based products, such as dokha and shisha. The proposed study aims to quantify the levels of nicotine and tar in different kinds of dokha and shisha products that are sold in the local marketplace. The amount of nicotine in dokha and shisha products can be quantitatively determined using a combination of the "kissling" and "silicotungstic acid" method proposed by Robert M. Chapin. The tar residue from the smoke sample was collected on a glass wool placed before the stopcock (tap) of a separatory funnel as the smoke passes through the inlet of an electronically controlled vacuum pump. The nicotine levels in dokha and shisha samples ranged from 23.83 to 52.80 mg/g and 0.80 to 20.52 mg/g, respectively. The nicotine level varies between different tobacco products. It varies from 0.5 to 19.5 mg/g in cigarettes, from 10.3 to 23.1 mg/g in snuff tobacco, from 11 to 18 mg/g in electronic cigarettes and from 2.9 to 16.6 mg/g in chewing tobacco. The tar levels in the dokha and shisha samples ranged from 21.6 to 45.02 mg/g and 1.68 to 11.87 mg/g, respectively. Smokers are at a high risk of getting lung cancer, chronic obstructive pulmonary disease, emphysema and coronary artery disease owing to the high levels of nicotine and tar present in dokha and shisha tobacco products. These findings contradict the widespread belief among teenagers that dokha and shisha tobacco products are safer alternatives to cigarettes.